Microbial epidemiology and clinical risk factors of carbapenemase-producing Enterobacterales amongst Irish patients from first detection in 2009 until 2020. Issue 3 (September 2022) - O'Connell, N.H.; Gasior, S.; Slevin, B.; Power, L.; Barrett, S.; Bhutta, S.I.; Minihan, B.; Powell, J.; Dunne, C.P.
Summary: Background: Carbapenemase producing Enterobacterales (CPE) are major public health threats. Aim: To review microbial epidemiology of CPE, as well as clinical risk factors and infections, amongst CPE positive patients over 12 years in an Irish tertiary hospital. Methods: Retrospective observational study of data extracted from a laboratory CPE database, electronic healthcare records and manual review of patient charts. Common risk factors, treatment regimens for all CPE related infections, and clinical outcomes were ascertained. Findings: Among CPE strains isolated from 460 patients, Klebsiella pneumoniae carbapenemase (KPC) was the carbapenemase most frequently detected, accounting for 87.4% (459) of all CPE enzymes. Citrobacter species 177 (33.7%) were the most common species harbouring this enzyme. 428 CPE positive patients (93%) were identified in the acute hospital setting; the most common risk factor for CPE acquisition was history of hospitalisation, observed in 305 (66%) cases. Thirty patients (6.5%) had confirmed infections post-acquisition, of which four were bloodstream infections. There were 19 subsequent episodes of non CPE-related bacteraemia in this cohort. All causal mortality at 30 days was 41 patients (8.9%). However, clinical review determined that CPE was an indirect associative factor in 8 patient deaths. Conclusions: In this tertiary hospital setting, microbial epidemiology is changing; with both OXA-48 enzymes and KPC-producing Citrobacter species becoming more prevalent. Whilst the burden of CPE related infections, especially bacteraemia, was low over the study period, it remains critical that basic infection prevention and control practices are adhered to lest the observed changes in epidemiology result in an increase in clinical manifestations.